Association Between Knowledge and Attitude of Contraceptive Acceptors and Side Effects of Three-Month Injectable Contraceptives at Private Practice - Fauza, Riska; Yuliana; Faridah (Bantayang Omni Cendekia, 2026)
Background: Injectable contraceptives are the most widely used family planning method in Indonesia, accounting for approximately 63.7% of all contraceptive users. However, the use of three-month injectable contraceptives is often associated with side effects such as dizziness, menstrual irregularities, bleeding, and weight gain, which may influence acceptors’ knowledge and attitudes. Objective: This study aimed to examine the association between knowledge and attitudes of contraceptive acceptors and the side effects of three-month injectable contraceptives at a private midwifery practice. Methods: This study employed an analytic cross-sectional design. The study was conducted over five days at Midwife Hj. Lindawati’s Practice in Kembang Tanjong District, with a total population of 144 acceptors. A sample of 59 respondents was selected using the Slovin formula. Data were collected using a structured questionnaire and analyzed using appropriate statistical tests to determine the association between variables. Results: The findings showed a statistically significant association between knowledge and the side effects of three-month injectable contraceptives (p = 0.002; p < 0.05). Similarly, a significant association was found between attitudes and the side effects of three-month injectable contraceptives (p = 0.002; p < 0.05). Conclusion: There is a significant association between knowledge and attitudes of contraceptive acceptors and the side effects of three-month injectable contraceptives. Improving knowledge and fostering positive attitudes among acceptors may help in managing and reducing the impact of these side effects.